WOMEN EMPOWERMENT MODEL THROUGH CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM - ADHIANTY NURJANAH

(untitled)
Empowerment of women which aims to enhance the role of women in development in Indonesia has been done. The government's commitment in 2000 was marked by issuing Presidential Decree Number 9 of 2000 on Gender Mainstreaming (PUG) in all areas of development for the implementation of the planning, preparation, implementation and evaluation of government policies that are gender responsive. Indonesian government's efforts to empower women through policy with gender perspective has actually been done. But in reality it turns out that there are imbalances and gender inequality in a variety of access and opportunity contributing to the development and take advantage of the development is still often the case, with women as the recipients of misfortunes (Hubeis, 2010). In empowering women in development, the government can not work alone, but the private sector / company is currently participating through Corporate Social Responsibility (CSR) program. Ideally Corporate Social Responsibility (CSR) program is a community development program that is able to empower marginalized groups in the society socio-economically. In general, the purpose of community development is to empower specific groups in the society, including women who are socio economically poor. This includes the research into the type of qualitative descriptive study. Studying the problems in society, research was conducted at PT Sari Husada Yogyakarta with specialization CSR Rumah Srikandi Program in Kampung Badran Yogyakarta. The results showed that women's empowerment efforts conducted by PT Sari Husada Yogyakarta through the Rumah Srikandi Corporate Social Responsibility (CSR) program with 3 pillars of the program : the Economic Development Program, Child Education Development, and Nutrition Development Program has been carried out. In empowering women, there are five dimensions that influence well-being, access to resources, participation, critical awareness and control women. The empowerment of women through the Rumah Srikandi CSR program in Badran Yogyakarta, still needs improvement, especially in the dimension of critical consciousness and control. Women empowerment model that can be done to overcome this is through (1). Critical awareness of women's empowerment. (2) Empowerment of women’s capacity and (3). Empowerment of women's entrepreneurship through a group approach.